Como nos tornamos gente? Escrevivências das memórias e resistências da juventude de Cariacica-ES (por uma educação aquilombada) - Conceição, Carlos Antonio (2023)
The research addresses the memories of resistance and powerful life of the black youth of Cariacica/ES. The research problem that guides the work is: how young black, poor and peripheral people form, “become People”, amidst the necropolitics that prevail today and that decimate so many black lives; social precariousness, which exiles thousands of young people from access to a dignified life; quality education, the means necessary to access, maintain and persevere in studies and in life. The objective of the research is to write down the forces that enhance the lifestyles of black youth in Cariacica (ES), which has been affected by the criminalization of poverty and political and social precariousness, to give visibility to the resistance that makes the affirmation of life possible. The study is qualitative in nature and was outlined by the principles that guide writing, highlighting the fact of tracing analytical paths, maps of meaning, during the actions of establishing relationships with work collaborators. The focus of the research is to understand how young people face social precariousness and how they see and experience formal and regular education. After listening to the writings, in which we sought to focus on the instituting forces established in the educational experiences of the young participants in the study, we can highlight that through actions such as a) facing fear by broadening the perspective of the present; b) Expand the sharing of dreams; c) expanding gestures of care for others and finally, d) learning and sharing the diversity that we are, operated in confronting the precariousness experienced, constituting important clues in the exercise of an quilomabada education practice.